Prevalence of fungal diseases of large cardamom (Amomum subulatum Roxb.) in Sikkim, India - SRIVASTAVA, L S (Journal of Spices and Aromatic Crops, 1995)
The information available on the prevalence of various fungal diseases of large cardamom (Amomum subulatum Roxb.) in Sikkim are discussed.